Social Media: Millenial Generation Alternative Solutions in Learning Religion During Covid-19 Pandemic - Ritonga, Mahyudin; Ritonga, Apri Wardana; Desrani, Ayu (Institut Agama Islam Negeri Imam Bonjol Padang, 2022)
The use of social media as a communication medium is not limited. In the era of technological development with the spread of the Covid-19 pandemic, social media is also used to access information about spiritual issues. This study aims to explore the use of social media as a religious learning solution for the millennial generation in the era of the spread of Covid-19. This study adopts a qualitative approach with a phenomenological method to the millennial generation's tendency to use social media. Data collection uses observation, interviews, and analysis studies of da’wah accounts on social media. The data analysis technique uses the theory of Miles and Huberman, namely collecting data, reducing, and presenting. Data validation uses data triangulation and data sources. This study shows that the millennial generation filters da’wah accounts on social media based on their understanding (manhaj). This research needs to be followed up by mapping the concept of da’wah through social media which is relevant for the millennial generation in Indonesia.